How is the Process of Mathematical Literacy Viewed From the Initial Mathematical Performance? - Kadarisma, Gida; Juandi, Dadang; Darhim, Darhim (Jurnal Pendidikan Progresif, 2024)
Abstract: How is the Process of Mathematical Literacy When Viewd From the Initial Mathematical Performance? The role of mathematics functionally in the context of everyday life which refers to the ability of individuals to respond to needs and obstacles in society is known as the conception of mathematical literacy. Mathematical literacy is an important aspect that every individual has to face the 21st century, there are 3 important processes in mathematical literacy, namely formulating, employ and interpreting mathematical results into everyday problems, besides that students' initial mathematical abilities are important and related to mathematical literacy. Therefore the aim of this research is to analyze the process of mathematical literacy in terms of initial mathematical abilities. This research is a qualitative descriptive study with a subject of 3 students consisting of 1 student each with high, medium and low initial math skills in junior high school students in Cimahi. The instruments used in this study were a Mathematical Literacy test instrument consisting of 3 questions, an initial mathematical performancetest and an interview guide. The results of this study indicate that students with low performance cannot carry out the 3 processes of mathematical literacy (Formulation, employ and interpreting), students with moderate abilities can formulate problems in mathematical form and use mathematical concepts for problem solving but are still wrong in doing calculations and unable to interpret the information contained in the table/diagram. Whereas for students with high initial mathematical performance, they can formulate everyday problems in mathematical representations, they can also use concepts, facts and procedures for problem solving but are not yet precise at the stage of interpreting and communicating in writing Keywords: mathematical literacy, initial mathematical performance.DOI: http://dx.doi.org/10.23960/jpp.v14.i1.202446